2015
DOI: 10.1515/plass-2015-0024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity and phylogeny of Triticum-Aegilops species possessing D genome revealed by SSR and ISSR markers

Abstract: The aim of this study is investigation the applicability of SSR and ISSR markers in evaluating the genetic relationships in twenty accessions ofAegilopsandTriticumspecies with D genome in different ploidy levels. Totally, 119 bands and 46 alleles were detected using ten primers for ISSR and SSR markers, respectively. Polymorphism Information Content values for all primers ranged from 0.345 to 0.375 with an average of 0.367 for SSR, and varied from 0.29 to 0.44 with the average 0.37 for ISSR marker. Analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 28 publications
6
9
0
Order By: Relevance
“…All three marker systems showed the highest PPL in the northwestern genotypes, indicating a high allelic diversity and the heterogeneity of these genotypes. Our results confirmed that the main center for the diversity of the genus Aegilops in Iran was most probably located in the north and northwest of the country [44].…”
Section: Discussionsupporting
confidence: 85%
“…All three marker systems showed the highest PPL in the northwestern genotypes, indicating a high allelic diversity and the heterogeneity of these genotypes. Our results confirmed that the main center for the diversity of the genus Aegilops in Iran was most probably located in the north and northwest of the country [44].…”
Section: Discussionsupporting
confidence: 85%
“…DNA analysis using ISSR and SCoT markers has proved to be an efficient and inexpensive way to provide molecular data to evaluate genetic variation, and it has been used successfully to determine genetic relationships for many plants [12,14,17,18,[30][31][32][33]. In the present study, the ISSR technique revealed higher mean PB (16.67) than SCoT (16.45).…”
Section: Polymorphism Detected By Issr and Scot Primersmentioning
confidence: 51%
“…Genetic diversity in the wheat germplasm opens up new scenarios to the discovery of useful genes or alleles and improvement of varieties with desirable traits, which include both farmer-and breed-preferred traits such as yield potential, large seed, high seed weight and tolerance to both biotic and abiotic stresses [21]. Previously, the genetic diversity and population structure of T. uraru populations have been studied using a large number of marker systems, including morphological characters [22], isozymes [23] and molecular markers [20,24,25].…”
Section: Introductionmentioning
confidence: 99%